2016
DOI: 10.1155/2016/4840301
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Reduced Graphene Oxide for Supercapacitor

Abstract: A facile method to synthesize highly reduced graphene oxide in solid phase was developed. The reduced graphene oxide was scarcely prepared in solid phase. Solid substances act as spacers and pillaring agents. Sheets can not be close to each other in reduction process, and sheets agglomeration might not form. After reduction reaction is complete, the spacers and pillaring agents are removed. The average interlayer spacing and surface area of product are bigger than those of reduced graphene oxide. The product h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…During the reduction of GO to rGO, we adopted the solid-phase reduction via sinking and leaving process, which renders the agglomeration of the GO sheets by minimizing the time of interaction for the rGO sheets, as it generally occurs in the case of solution-based reduction methods, where the rGO sheets interact at a faster rate and result in agglomeration. 23 Generally, it is observed that during the solution-phase reduction of GO to rGO, sheets are free to interact with each other, thereby resulting in agglomeration that leads to performance reduction, while the solid-state reduction of the GO also restricts the free movement of the rGO sheets to protect themselves from agglomeration. Thereby, in the present process of fabrication, rGO may use its maximum surface area, which can enhance the performance of the supercapacitor.…”
Section: Methodsmentioning
confidence: 99%
“…During the reduction of GO to rGO, we adopted the solid-phase reduction via sinking and leaving process, which renders the agglomeration of the GO sheets by minimizing the time of interaction for the rGO sheets, as it generally occurs in the case of solution-based reduction methods, where the rGO sheets interact at a faster rate and result in agglomeration. 23 Generally, it is observed that during the solution-phase reduction of GO to rGO, sheets are free to interact with each other, thereby resulting in agglomeration that leads to performance reduction, while the solid-state reduction of the GO also restricts the free movement of the rGO sheets to protect themselves from agglomeration. Thereby, in the present process of fabrication, rGO may use its maximum surface area, which can enhance the performance of the supercapacitor.…”
Section: Methodsmentioning
confidence: 99%
“…The 24° peak corresponding to (002) diffraction plane indicates that reduction was successful while the 43° peak corresponding to (100) diffraction plane indicates high extent of reduction with interlayer spacing of 0.38 nm and 0.36 nm respectively [ 11 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In connection with the above, we can distinguish methods consisting in the grinding of graphite classified as top-down and regrouping/condensation of carbon atoms classified as bottomup. The main top-down and bottom-up graphene production techniques are: dry graphite delamination [4,5], liquid phase delamination [6,7], growth on silicon carbide [8], chemical gas phase deposition (CVD) [9][10][11][12], epitaxial methods [13], thermal conversion of amorphous carbon and other carbon precursors [14], chemical synthesis [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%